Synchrotron x-ray pair distribution function: A tool to characterize cement gels - Cuesta-García, Ana María; Zea-Garcia, Jesus D.; Londono-Zuluaga, Diana; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; García-Aranda, Miguel Ángel (My University, 2018)
Cement matrices contain large amounts of crystalline phases jointly with amorphous and/or nanocrystalline phases. Consequently, their analyses are very challenging. Synchrotron powder diffraction in combination with the pair distribution function (PDF) methodology is very useful to characterize such complex cement pastes. This work is focused on the study of the short and medium range atomic arrangement(s) in the different nanocrystalline gels which are present in the cement pastes through total scattering Pair Distribution Function quantitative phase analyses.
Keywords: Cemento; Pair distribution function; Cementitious materials; Nanocrystaline gels